2018
DOI: 10.1097/mao.0000000000001813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Characteristics and Surgical Outcomes of Cystic and Solid Vestibular Schwannomas

Abstract: CVSs tend to be larger than SVSs. Tumor volume, not cystic component, is thought to be a major determinant of surgical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
1
17
1
Order By: Relevance
“…It has been demonstrated that the volume increase of VS is not merely based on cell proliferation, but is also implicated with (neo)vascularization, intratumoral hemorrhage, cyst formation and inflammatory reaction ( 32 , 101 , 102 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the volume increase of VS is not merely based on cell proliferation, but is also implicated with (neo)vascularization, intratumoral hemorrhage, cyst formation and inflammatory reaction ( 32 , 101 , 102 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the volume increase of VS is not merely based on cell proliferation, but is also implicated with (neo)vascularization, intratumoral hemorrhage, cyst formation and inflammatory reaction (32,101,102). On the one hand, merlin initiates the Hippo pathway by directly activating mammalian STE20-like protein (MST1/2), which in turn phosphorylates large tumor suppressor homolog 1/2 (LATS1/2), or by recruiting LATS 1/2 to the plasma membrane for phosphorylation by MST1/2 kinases.…”
Section: Inflammatory Signalmentioning
confidence: 99%
“…Large cystic VS account for 10-20% of all VS and are thought to be characterized by a more rapid growth and worse surgical outcome, mostly related to their larger size and greater adhesion to the surrounding tissues [54], and should be distinguished from solid VS.…”
Section: Introductionmentioning
confidence: 99%
“…In our data, this discrepancy was likely due to cVS patients with worse long-term FN outcome versus most sVS patients, who improved in their long-term FN function. Compared with the existing literature, which focuses primarily on a single time point for follow-up, we demonstrate in our data that cVS patients trended toward worse outcomes even at their first postoperative follow-up appointments, which has important implications for FN rehabilitation and patient counseling 23 . It may be possible that during dissection of cystic tumors, there is an increased likelihood of traction injury to the surrounding cranial nerves (facial and cochleovestibular) as the cystic tumors are inherently more adherent.…”
Section: Discussionmentioning
confidence: 44%
“…Although cystic tumors were historically associated with worse FN outcomes, 6 recent studies have begun to question this traditional dogma 23–25 . These studies argue that differences in outcomes between cVS and sVS are likely secondary to differences in tumor volume rather than the presence of the cyst.…”
Section: Discussionmentioning
confidence: 99%